1984
DOI: 10.1055/s-2008-1036665
|View full text |Cite
|
Sign up to set email alerts
|

Wirkung einer Lactobazillus-Immuntherapie auf die Genitalinfektion der Frau (SolcoTrichovac/Gynatren)

Abstract: In view of the high cure rates of Trichomonas vaginitis after vaccination with the immunotherapeutic drug Solco Trichovac Gynatren, the therapeutic efficacy of this regimen in nonspecific vaginitis was investigated. 94 patients were treated in a multicentre study. Concurrent with a decrease of pathogens, the growth of a normal lactobacilli flora was observed. The degree of vaginal purity according to Schröder and the vaginal pH returned to normal. A cure or at least a marked improvement of symptoms was documen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

1984
1984
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…It has recently been reported that a novel method of treatment, based on immunological considerations, can be effective in combating non-specific vaginitis. This treatment consists of vaccination with a preparation containing several special strains of Lacto bacillus acidophilus [1,2], This vaccine was initially intended for the treat ment and prevention of relapses of trichomoniasis [3], but several clinical trials have also shown its efficacy in the treatment of non-specific vaginitis [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been reported that a novel method of treatment, based on immunological considerations, can be effective in combating non-specific vaginitis. This treatment consists of vaccination with a preparation containing several special strains of Lacto bacillus acidophilus [1,2], This vaccine was initially intended for the treat ment and prevention of relapses of trichomoniasis [3], but several clinical trials have also shown its efficacy in the treatment of non-specific vaginitis [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The cure rate has been reported 90 % (Bonilla-Musoles 1984) and 80 % (Karkut 1984) in vaccine therapy. Immunotherapy of trichomoniasis has some advantages over metronidazole which are the prophylactic effect of vaccine on patients about reinfection and recurrence (Bonilla-Musoles 1984).…”
Section: Trichomoniasismentioning
confidence: 99%
“…Dabei kann vor allem der sogenannte «unspezifische» Fluor vaginalis, bei dem es nicht gelingt, einen ursächli chen Erreger zu identifizieren, grosse therapeutische Probleme bedeuten [2, 3, 5, [6][7][8][9], Die Laktobazillen, von Döderlein [1] 1892 erstmals beschrieben, stel len die physiologische Schutzfunktion der Scheide vor lokalen und aszendierenden Infektionen dar [6,10]. Der biologische Reaktionsmechanismus der Scheide ist an eine intakte Döderleinsche Flora (Lactobacillus acido philus) gebunden.…”
Section: Introductionunclassified
“…Jede Störung dieses Regelmecha nismus hat eine Herabsetzung der Schutz-und Barrierefunktion zur Folge und begünstigt somit die Entstehung von Fluor und Kolpitis [2, 6,7,10].…”
Section: Introductionunclassified
See 1 more Smart Citation